Gustave Flaubert - Roe, David (New York : Macmillan, 1989)
A collection of fourteen critical essays on the French writer, arranged in chronological order of their original publication.
Includes index.
Bibliography: p. 273-279.
Keywords: Flaubert, Gustave, -- 1821-1880 -- Criticism and interpretation; Flaubert, Gustave, -- 1821-1880 -- Criticism and interpretation; French literature -- History and criticism